<htm>A vegetação na Reserva Mata Viva, Curitiba, Paraná, Brasil</htm> - Reginato, Marcelo; Matos, Fernando Bittencourt; Lindoso, Galiana da Silveira; Souza, Caroline M. Fogaça de; Prevedello, Jayme A.; Morais, Juliana Wilgozz; Evangelista, Paulo H. Labiak (Acta Biológica Paranaense, 2008)
<htm>A vegetação na Reserva Mata Viva, Curitiba, Paraná, Brasil</htm>